Cleansing Composition Comprising Unmodified Clay and Polyglycerol Surfactant - Patent application

A cleansing composition combining unmodified trioctahedral smectites with short-chain polyglycerol surfactants addresses stability and foam texture issues, providing stable, creamy foam with enhanced sebum absorption and anti-oil skin effects.

JP7628613B2Active Publication Date: 2025-02-10LOREAL SA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023538127
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-22
Filing Date
2021-12-21
Publication Date
2025-02-10
Estimated Expiration
2041-12-21

AI Technical Summary

Technical Problem

Current foaming cleansing products suffer from precipitation issues due to high clay content, affecting stability and functional properties, while also lacking satisfactory foam texture and anti-oil skin effects.

Method used

A cleansing composition is formulated using unmodified trioctahedral smectites combined with short-chain polyglycerol surfactants, maintaining a mass ratio of ester to clay greater than 1, which forms a stable aqueous gel.

Benefits of technology

The composition achieves stable, creamy foam with effective sebum absorption, enhancing skin cleansing and maintaining a matte skin effect without precipitation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628613000001
    Figure 0007628613000001
  • Figure 0007628613000002
    Figure 0007628613000002
  • Figure 0007628613000003
    Figure 0007628613000003
Patent Text Reader

Abstract

Cleansing composition comprising an unmodified clay and a polyglycerol surfactant.The subject of the present invention is a cosmetic composition, in particular a cosmetic composition for cleansing the skin and / or its appendages, comprising, in an aqueous physiologically acceptable medium, at least one unmodified clay chosen from trioctahedral smectites and at least one ester chosen from esters of fatty acids containing from (4) to (16) carbon atoms and of polyglycerol containing from (2) to (10) glycerol units, the mass ratio ester:clay being strictly greater than (1).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to cleansing compositions comprising clay. [Background technology]

[0002] Skin cleansing is very important for skin care.Cleansing must be as effective as possible.Because fatty residues, such as excess sebum or residues of cosmetics used daily, can accumulate in skin folds and block skin pores, causing comedones.Effective skin cleansing is especially achieved by using foaming products.

[0003] The foaming cleansing products currently available commercially have the form of cake, gel or foaming liquid. They generally contain either soap, which has the advantage of providing creamy and voluminous foam, or a combination of foaming surfactant and stabilizer. In particular, compositions in the form of gel often contain water, a water-soluble polymer and a mixture of surfactants. To provide anti-oily skin effect, loading materials can also be added to the composition, and these loading materials actually remain on the skin to absorb sebum and / or sweat, thus maintaining the facial mattifying effect. Loading materials include clays in particular.

[0004] However, current compositions have a high clay content, which can result in problems with settling, which has a detrimental effect on the organoleptic properties of the composition.

[0005] Therefore, it is necessary to have a cleansing composition for human keratinous materials, preferably facial and / or body skin, and / or hair, which has a satisfactory foam texture, especially a creamy foam, while still being stable and having good cleansing properties.It is also necessary to have a cleansing composition with anti-oily skin properties and improved stability, especially reduced precipitation problems.In particular, there is a need for foaming cleansing compositions with little or no syneresis. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Bergaya F., Lagaly G., Handbook of Clay Science, 2nd Edition, A. Fundamentals, Elsevier Ltd., 2013. Summary of the Invention [Problem to be solved by the invention]

[0007] The aim of the present invention is to propose such a composition. The composition according to the invention does not have the disadvantages of the prior art and in particular has good application qualities (foam quality and creaminess, anti-oily skin effect) and is stable (i.e. does not syneresis). [Means for solving the problem]

[0008] Indeed, the inventors have demonstrated that the combination of an unmodified clay selected from trioctahedral smectites with short chain polyglycerol surfactants (i.e., in the C4-C16 range) provides a cosmetic composition that meets these needs.

[0009] The subject of the present invention is therefore a cosmetic composition, in particular a cosmetic composition for cleansing the skin and / or its appendages, which comprises, in an aqueous physiologically acceptable medium: at least one unmodified clay selected from trioctahedral smectites, and at least one ester selected from esters of fatty acids containing 4 to 16 carbon atoms and polyglycerol containing 2 to 10 glycerol units. Including, the mass ratio of ester:clay is strictly greater than 1; It is a composition.

[0010] Another subject of the present invention is a method for cleansing the skin and / or skin appendages, comprising the step of applying to the skin and / or skin appendages a composition according to the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] By "physiologically acceptable medium" is meant a medium that is compatible with the skin and / or its appendages.

[0012] Unmodified Clay The composition according to the invention comprises at least one unmodified clay chosen from trioctahedral smectites.

[0013] This clay belongs to the phyllosilicates with a 2:1 sheet structure. The classification of clays is mentioned in the following work: Bergaya F., Lagaly G., "Handbook of Clay Science", 2nd Edition, A. Fundamentals, Elsevier Ltd., 2013.

[0014] Phyllosilicates are a group of silicate minerals built by stacking tetrahedral layers ("T") that share three of their four vertices (the "bottom" oxygen) and connect at the fourth vertex (the "top" oxygen) to an octahedral layer ("O") occupied by a different cation. In phyllosilicates with the TOT structure, an octahedral layer O is intercalated between two tetrahedral layers T.

[0015] The 2:1 sheet structure is also called the TOT structure, where T is a tetrahedral layer and O is an octahedral layer.

[0016] The unmodified clays according to the invention belong to the smectites.

[0017] The structure of smectites depends on the state of hydration of the clay and is distinguished from other phyllosilicates with a 2:1 sheet structure by the presence of interlayer spaces between the bonds of each TOT sheet, into which interlayer cations are inserted. Smectites are also often called "swellable" clays. Preferably, the interlayer cations are Ca 2+ , Mg 2+ , Na + and Li + is selected from.

[0018] The unmodified clays according to the invention are selected from trioctahedral smectites.

[0019] Trioctahedral smectites are characterized by the fact that all the octahedral sites of the TOT structure are occupied mainly by divalent cations. Preferably, the divalent cations at the octahedral sites are Mg 2+ and Fe 2+ is selected from.

[0020] In particular, the unmodified clays according to the invention are trioctahedral smectites that can be exfoliated or "activated" in the presence of water, thus forming aqueous gels due to the presence of interlayer cations in the structure.

[0021] When water comes into contact with the unmodified clay suitable for the present invention, it hydrates the sheets of the unmodified clay, thus resulting in an expansion of the distance between the sheets. Separation of the sheets then occurs, possibly by exfoliation and / or delamination mechanisms. An aqueous gel is then obtained. In practice, a content of this particular type of clay in the range of 0.5% to 10% by weight, relative to the total weight of the composition, allows to obtain a gelled aqueous phase in the composition according to the present invention.

[0022] Preferably, the clay according to the invention has an amount of SiO 2 of at least 30% by weight, preferably between 35% and 65% by weight, relative to the total weight of the clay. 2 and MgO in an amount of 10% or more, preferably between 15% and 30% by weight.

[0023] According to a preferred embodiment, the clay according to the invention contains 35% to 65% by weight of SiO 2 relative to the total weight of the unmodified clay. 2 and 15% to 30% by mass of MgO based on the total mass of the unmodified clay.

[0024] Preferably, in the clay according to the invention, SiO 2 The / MgO mass ratio is comprised between 1 and 3, preferably between 1.5 and 2.5, preferably between 1.8 and 2.4.

[0025] Preferably, the clay according to the invention contains an amount of Al comprised between 0% and 15% by weight relative to the total weight of the clay. 2 O 3 Further includes:

[0026] According to a first alternative, the clay suitable for the invention is Al 2 O 3 It lacks (does not contain).

[0027] According to a second alternative, the clays suitable for the invention contain between 0.1% and 15% by weight, preferably between 8% and 12% by weight, of Al relative to the total weight of the unmodified clay. 2 O 3 may include.

[0028] According to another preferred embodiment, the clay suitable for the present invention contains Al 2 O 3 If present, SiO 2 / Al 2 O 3 The mass ratio is strictly greater than or equal to 3.

[0029] Preferably, the clays according to the invention have a density of less than 2.7. Density (i.e. specific gravity) is a very important property of minerals, but its calculation is fairly straightforward. Density has no units and is measured using a variety of instruments and techniques, which are covered in most mineralogy handbooks. Of these methods, the Jolly balance and beam balance are the most suitable for working with mineral samples. The instruments for obtaining these measurements are simple and can be constructed at low cost (Sinkankas, 1966). Density satisfies the following calculation:

[0030] [Formula 1] Density = (mass in air) / (mass in air - mass in water)

[0031] According to a particular embodiment, the unmodified clays suitable for the present invention have the following general molecular formula:

[0032]

number

[0033] [In the formula, M 4+ is a cation, preferably Si 4+ represents M 3+ is a cation, preferably Al 3+ represents M 2+ is a cation, preferably Fe 2+ or Mg 2+ represents M + is a cation, preferably Li + represents X is an interlayer cation, preferably Ca 2+ , Na + , Li + or a mixture thereof, x represents the tetrahedral substitution rate, y represents the octahedral substitution rate, k represents the valence of the interlayer cation X; n represents an integer, preferably 0 to 100. has.

[0034] Unmodified clays suitable for the present invention are generally available in powder form.

[0035] Preferably, the unmodified clay is selected from unmodified hectorite, unmodified stevensite and unmodified saponite.

[0036] Advantageously, the unmodified clay is unmodified hectorite. Unmodified hectorite has the following formula: Na x (Mg 3-x ,Li x )Si 4 O 10 (OH) 2 [x is comprised between 0.2 and 0.4, and is preferably equal to 0.3].

[0037] Preferably, the clay of the composition according to the invention is different from sauconite, sobotkite, talc and montmorillonite.

[0038] The term unmodified clay means a natural or synthetic clay that has not been subjected to any modification of any type. For example, when the unmodified clay suitable for the present invention is unmodified hectorite, the unmodified hectorite is C 10 ~C 22 It is different from hectorite modified with fatty acid ammonium chloride, for example hectorite modified with distearyl dimethyl ammonium chloride. According to an embodiment, the non-modified clay suitable for the present invention is a synthetic clay.

[0039] According to a preferred embodiment, the unmodified clay suitable for the present invention is a natural clay, preferably natural hectorite.

[0040] The term modified clay refers to silicates whose oleophilicity in the sheet has been increased by ion exchange reaction with, for example, a quaternary ammonium salt, preferably a quaternary ammonium chloride, such as, for example, benzyl dimethylstearyl ammonium chloride or a quaternary ammonium chloride of the formula

[0041] [ka]

[0042] [In the formula, R 1 groups are independently selected from C12 to C20 saturated linear alkyl groups. The modified clay is, for example, disteardimonium hectorite or stearalkonium hectorite.

[0043] Preferably, the composition according to the present invention is substantially free of modified clay, preferably substantially free of disteardimonium hectorite and stearalkonium hectorite.By "substantially free" is meant that the composition contains less than 0.1% by weight, preferably less than 0.05% by weight, preferably less than 0.01% by weight of modified clay, based on the total weight of the composition.Preferably, the composition according to the present invention is completely free of modified clay.

[0044] Preferably, the clay is present in a content between 0.1% and 10% by weight, preferably between 0.5% and 8% by weight, preferably between 1% and 5% by weight and advantageously between 1.5% and 3% by weight relative to the total weight of the composition.

[0045] As unmodified clay, and more particularly as unmodified hectorite, it is possible to use those sold under the names Bentone EW or HYDROCLAY 2000 LO by the company Elementis.

[0046] Esters of fatty acids and certain polyglycerols The composition according to the invention also comprises at least one ester chosen from esters of fatty acids containing from 4 to 16 carbon atoms and of polyglycerols containing from 2 to 10 glycerol units.

[0047] Preferably, the esters according to the invention selected from the esters of fatty acids containing from 4 to 16 carbon atoms and of polyglycerols containing from 2 to 10 glycerol units are mono- or diesters, preferably mono-esters.

[0048] The term "polyglycerol" refers to a glyceryl polymer that is a linear chain of glycerol units.

[0049] The esters more particularly contemplated by the present invention are those resulting from the esterification of polyglycerol with a carboxylic acid having a carbon chain of a given length.

[0050] The carboxylic acids may be linear or branched, saturated or unsaturated.

[0051] Preferably, the carboxylic acid is a straight chain monocarboxylic acid.

[0052] Generally, these esters are derived from the esterification of at least one hydroxyl functional group of a polyglycerol with a carboxylic acid having a carbon chain of a given length.

[0053] According to one particular embodiment, the esters suitable for this invention may be derived from the esterification of polyglycerol with one or more identical or different carboxylic acids. The esters may be hydroxylated monoesters, hydroxylated diesters, hydroxylated triesters or mixtures thereof.

[0054] The esters are formed from (i) at least one fatty acid containing an alkyl or alkenyl chain containing from 4 to 16 carbon atoms (also called a C4-C16 fatty acid) and (ii) from 2 to 10 glycerol units.

[0055] Preferably, the fatty acid contains from 6 to 14 carbon atoms, preferably from 8 to 12 carbon atoms. Preferably, the fatty acid is saturated and contains a linear alkyl chain.

[0056] Preferably, such fatty acids containing from 4 to 16 carbon atoms are selected from capric acid, lauric acid, myristic acid and palmitic acid.

[0057] Preferably the fatty acid is C10, preferably capric acid.

[0058] Preferably, the ester comprises 3 to 6 glycerol units, preferably 4 glycerol units.

[0059] In a preferred embodiment of the invention, the ester is an ester of a fatty acid containing 10 carbon atoms and a polyglycerol containing 4 glycerol units.

[0060] More preferably, the ester is polyglyceryl monocaprate containing four glycerol units, ie, polyglyceryl monocaprate-4.

[0061] A commercial product based mainly on polyglyceryl-4 monocaprate, i.e. PG-4 caprate, is available from EVONIK GOLDSCHMIDT under the trade name TEGOSOFT PC 41.

[0062] According to another embodiment of the invention, the ester is an ester of a fatty acid containing 12 carbon atoms with a polyglycerol containing 5 glycerol units, preferably a polyglyceryl monolaurate containing 5 glycerol units, i.e. polyglyceryl-5 monolaurate. A commercial product based mainly on polyglyceryl monolaurate, i.e. PG-5 laurate, is available from Taiyo Kagaku Co., Ltd. under the trade name SUNSOFT A-121E-C®.

[0063] The ester of fatty acid and polyglycerol may be present in the composition according to the present invention in a content ranging from 0.5% to 10% by mass, preferably from 1% to 8% by mass, more preferably from 2% to 6% by mass, relative to the total mass of the composition.

[0064] According to the invention, the mass ratio (ester:clay) of the composition is strictly greater than 1. It is preferably greater than or equal to 1.05, preferably greater than or equal to 1.5, preferably greater than or equal to 1.8.

[0065] polymer Polymers that can be used in the compositions according to the invention are, for example, oligo- or polysaccharides, acrylic and / or methacrylic polymers or copolymers, carboxyvinyl polymers, polyglyceryl acrylates or polyglyceryl methacrylates.

[0066] Specific polymers that may be mentioned are the carboxyvinyl polymers sold by GOODRICH under the trade name CARBOPOL or by SIGMA under the trade name SYNTHALEN K, the acrylic acid / ethyl acrylate copolymer, the acrylic acid / stearyl methacrylate copolymer, the polyglyceryl methacrylate sold by GUARDIAN under the trade name LUBRAJEL or the polyglyceryl acrylate sold by HISPANO CHIMICA under the trade name HISPAGEL.

[0067] Preferably, the composition of the invention comprises at least one polysaccharide or oligosaccharide, preferably at least one polysaccharide, which is a hydrophilic thickening polymer.

[0068] Preferably, the polysaccharide is selected from natural polymers, such as cellulose derivatives, e.g. carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxymethylcellulose, hydroxypropylmethylcellulose, ethylhydroxyethylcellulose, xanthan gum, carob gum, gum arabic, acacia gum, natural and modified cationic scleroglucan, gellan, konjac, rhamsan gum, alginates, pectins, karaya gum, modified or unmodified starches, carrageenans, galactomannans, pullulan, modified or unmodified guar gum, and derivatives thereof, such as hydroxypropyl guar, hyaluronates, e.g. sodium hyaluronate, arabinogalactans, e.g. gum arabic, xanthan gum or exopolysaccharides (polysaccharides of microbial origin), including dextran, fructans, e.g. inulin, agar agar.

[0069] Preferably, the oligosaccharide is selected from diholosides or triholosides, such as, in particular, the diholosides or triholosides of cellobiose, gentiobiose, inulobiose, isomaltose, isomaltulose, kojibiose, lactose, laminaribiose, leucrose, maltose, maltulose, melibiose, nigerose, robinose, rutinose, saccharose, sophorose, trehalose, trehalulose, turanose, erlose, fucosyllactose, gentianose, inulotriose, 1-kestrose, 6-kestrose, maltotriose, mannotriose, melezitose, neokestose, panose, raffinose, rhamninose, cyclodextrin, stachyose or verbascose.

[0070] Preferably, the composition of the invention comprises at least one polysaccharide, which is chosen from alginates and natural gums, such as xanthan gum.

[0071] The polymer, preferably a polysaccharide, may be present in the composition according to the invention in a content ranging from 0.1% to 10% by weight, preferably in the range from 0.5% to 7% by weight, preferably in the range from 0.7% to 3% by weight, relative to the total weight of the composition.

[0072] aqueous phase The compositions according to the invention comprise a physiologically acceptable aqueous phase which forms a physiologically acceptable aqueous medium.

[0073] The composition according to the invention preferably comprises an aqueous phase comprising water and optionally one or more organic solvents soluble in water at 25° C. These solvents may advantageously be chosen, for example, from C2-C4 linear or branched alkanols, such as ethanol and isopropanol, propanol, butanol; polyols, in particular polyols having from 2 to 20 carbon atoms, preferably from 2 to 6 carbon atoms. This polyol may be chosen from glycerin and its derivatives, and glycols and its derivatives. The polyols may be chosen from the group consisting of glycerin, diglycerin, polyglycerin, diethylene glycol, propylene glycol, dipropylene glycol, butylene glycol, pentylene glycol, hexylene glycol, 1,3-propanediol, 1,5-pentanediol, octane 1,2-diol, polyethylene glycols, in particular polyethylene glycols having from 5 to 50 ethylene oxide groups, and sugars, such as sorbitol, and mixtures thereof.

[0074] The composition generally contains 40% to 98% by mass, preferably 60% to 95% by mass, and preferably 70% to 93% by mass of water relative to the total mass of the composition.

[0075] The amount of organic solvent may range, for example, from 0.01 to 15% by weight, preferably from 0.5% to 13% by weight, and better still from 1 to 10% by weight, relative to the total weight of the composition.

[0076] Preferably, the composition according to the invention is an aqueous gel.

[0077] Furthermore, the composition according to the invention may comprise one or more conventional cosmetic additives, in particular those chosen from fatty substances, emollients, antioxidants, active agents, stabilizers, sequestering agents, moisturizers, vitamins, fragrances, preservatives, alkalizing or acidifying agents, or any other ingredient usually used for cosmetics and / or dermatology, in particular for the manufacture of compositions in the form of an aqueous gel.

[0078] Preferably, the composition according to the invention is substantially free of polymers of synthetic origin. By "substantially free" is meant that the composition comprises less than 1% by weight, preferably less than 0.5% by weight, preferably less than 0.1% by weight, of polymers of synthetic origin, relative to the total weight of the total composition. Preferably, the composition according to the invention is completely free of polymers of synthetic origin.

[0079] Preferably, the composition according to the present invention is substantially free of alkyl polyglycoside surfactant. By "substantially free" is meant that the composition contains less than 1% by weight, preferably less than 0.5% by weight, preferably less than 0.1% by weight of alkyl polyglycoside surfactant, based on the total weight of the composition.Preferably, the composition according to the present invention is completely free of alkyl polyglycoside surfactant.

[0080] Another subject of the present invention is a method for cleansing the skin and / or skin appendages, comprising the step of applying to the skin and / or skin appendages a composition according to the invention, which is preferably rinsed.

[0081] Consequently, preferably, the method for cleansing the skin and / or skin appendages according to the present invention comprises the step of applying a composition according to the present invention to the skin and / or skin appendages, followed by rinsing the skin and / or skin appendages.

[0082] The expressions "between...", "within the range of..." and "ranging from" and "to..." should be understood to include limits unless otherwise specified.

[0083] Specific, but non-limiting, examples illustrating the present invention are now provided.

[0084] Unless otherwise specified, pressure in the examples is atmospheric pressure. Unless otherwise specified, percentages are expressed by weight relative to the total weight of the composition (% w / w). EXAMPLES

[0085] Example 1 Characterization of natural unmodified clays according to the invention The gel / aqueous gel is prepared according to the following protocol: 1. Preparation of a mixture of water and 2% by weight of active substance (for each of the components as per table 1 below): mixing under rayneri (rotor / stator) at 3,000 rpm for 10 minutes; 2. Carry out sample preparation by dilution: i.e. in a mixer, mix for 3 min at 3,500 rpm (100 g); 3. At t=24h, observation / photography and rheological measurements (except for montmorillonite).

[0086] [Table 1]

[0087] The results are as follows.

[0088] [Table 2]

[0089] These results demonstrate that only unmodified hectorite according to the invention is capable of forming a composition in the form of an aqueous gel.

[0090] Example 2 Evaluation of the sebum absorption properties of compositions according to the invention versus comparative compositions Composition C1 according to the invention and comparative composition C * is prepared according to the following protocol using the ingredients mentioned in the table below (Table 3).

[0091] The hectorite or kaolin is dispersed in a water / glycerin mixture heated to 60°C using a rotator for 10 minutes. The mixture is cooled to room temperature. The sodium alginate is dispersed using a rotator and allowed to hydrate for 5 minutes. Finally, the surfactant is added, followed by the preservative and fragrance.

[0092] [Table 3]

[0093] Compositions C1 and C * The sebum absorption properties of the compositions were evaluated. The following test protocol models the behavior of the compositions over time in response to a sebum / sweat mixture on the skin. 1) A sebum / sweat mixture, which approximates the sebum film of the skin, is modeled by preparing a water / oleic acid / oleth-10 mixture (respective mass ratio: 79 / 20 / 1) from Vichy spring. 2) A film 100 μm thick is spread onto a DURAPORE hydrophobic filter with a 0.22 μm GVHP membrane filter (trade reference: GVHP00010) using an automatic applicator. The film is dried in an oven at 40° C. for 24 hours. 3) The brightness of the dried film is measured at 60° using a brightness meter (BYK). 4) Spray the film with a Vichy spring water / oleic acid / oleth-10 mixture once the mixture has returned to room temperature. 5) 6 minutes after spraying, the brightness of the film is measured at 60° using a brightness meter (BYK), then the film is sprayed again and the brightness is measured again 6 minutes after the second spray, then the film is sprayed a third time and the brightness is measured again 6 minutes after the third spray. The measured value is called the brightness unit UB. 6) Calculate the performance index, whereby compositions C1 and C * The performance of the system can be quantified.

[0094] For comparison, a negative reference (gel containing amino-propane-sulfonic acid (AMPS) and no loading material, index=0) and a positive reference (AMPS gel containing 2% aerogel, index=100) were selected.

[0095] Thus, for each composition, an index is calculated and placed on a scale of 0 to 100. If the index is greater than 100, this means that the composition tested is more effective than the positive reference.

[0096] The index is calculated using the following formula:

[0097]

number

[0098] The results obtained are shown in the table below (Table 4).

[0099] [Table 4]

[0100] The values ​​in the first column correspond to the brightness of the dry film before spraying the solution. The second value is the brightness 6 minutes after the first spray, with the corresponding performance index following in the third column. The values ​​in the fourth column correspond to the brightness 6 minutes after the second spray. The values ​​in the sixth column correspond to the brightness 6 minutes after the third spray.

[0101] This results in a large variation in the lightness values ​​when the clay used is kaolin, resulting in average to low performance indices depending on the number of sprays. With hectorite, the lightness increases much stronger. The performance index of the formulation C1 according to the invention is very good after the first spray and remains satisfactory thereafter. Hectorite is therefore able to absorb a much larger amount of artificial sebum than kaolin and has a clearly less effect on the lightness of the film (and therefore the skin).

[0102] Example 3 Evaluation of the foaming properties of compositions according to the invention versus comparative compositions Composition F1 according to the invention and comparative compositions F2 to F4 are prepared according to the protocol of Example 2 using the components mentioned in the table below.

[0103] All of these compositions are gels.

[0104] [Table 5]

[0105] The gels were evaluated for foam texture (hardness). "Hardness" refers to the force required to reach a given deformation of the surface of the tested product. This force is expressed in grams (g). Hardness measurements were taken using a Stable Micro Systems TA.XT plus brand texturometer.

[0106] The test was carried out as follows. Foam formation: In a 400 ml beaker, 30 g of the formulation is diluted 3 times with tap water.

[0107] A Braun (600w Turbo) mixer (speed 1, setting 15) is then used to generate a foam.

[0108] The density of the foam is then measured using a texturometer. The measurements are taken by piercing with a texturometer of the brand TA.XT plus manufactured by Stable Micro Systems using a set of Plexiglas bottles referenced A / EB (diameter 50 mm) + piston (diameter 45 mm).

[0109] Immediately after foam generation at T=2 minutes, the marysette is used to fill the foam piercing bottle, level it and then apply the weight.

[0110] Measurement protocol: Measurement threshold: 5g, Movement: 40mm, Sensor descending speed: 40mm s -1 , Measurement: Pull out

[0111] The results are presented in the table below (Table 6).

[0112] [Table 6]

[0113] The higher the measurement, the stiffer the resulting lather and the creamier the product will be upon application.

[0114] It can be seen that the maximum value is obtained with Polyglyceryl-4 caprate (formulation F1 according to the invention), which therefore gives the creamiest texture compared to the other surfactants evaluated.

Claims

1. A cosmetic composition, in particular a cosmetic composition for cleansing the skin and / or skin appendages, which is an aqueous gel, comprising in an aqueous physiologically acceptable medium: at least one unmodified clay selected from unmodified hectorite, and at least one ester selected from monoesters of fatty acids containing from 4 to 16 carbon atoms and polyglycerols containing from 3 to 6 glycerol units. Including, the mass ratio of ester:clay is strictly greater than 1; composition.

2. The unmodified clay has an amount of SiO of 30% by weight or more based on the total weight of the clay. 2 and MgO in an amount of 10% by weight or more.

3. Unmodified clay has an SiO content between 1 and 3. 2 3. The composition according to claim 2, characterized in that it comprises a / MgO mass ratio.

4. The unmodified clay contains between 0% and 15% Al by weight relative to the total weight of the clay. 2 O 3 The composition according to any one of claims 1 to 3, further comprising:

5. 5. Composition according to claim 1, characterized in that the unmodified clay is present in a content ranging from 0.1% to 10% by weight relative to the total weight of the composition.

6. 6. The composition according to claim 1, wherein the ester is formed from (i) at least one fatty acid comprising an alkyl or alkenyl chain containing from 6 to 14 carbon atoms and (ii) from 3 to 6 glycerol units.

7. A composition according to claim 1, characterized in that the ester is an ester of a fatty acid containing 10 carbon atoms and a polyglycerol containing 4 glycerol units.

8. A composition according to claim 1, characterized in that the ester is polyglyceryl monocaprate containing four glycerol units, i.e. polyglyceryl monocaprate-4.

9. 9. The composition according to claim 1, wherein the ester is present in a content ranging from 0.5% to 10% by weight relative to the total weight of the composition.

10. 10. The composition according to claim 1, characterized in that the ester:clay mass ratio is greater than or equal to 1.

05.

11. 11. Composition according to any one of claims 1 to 10, characterized in that it comprises at least one polymer chosen from oligo- or polysaccharides, acrylic and / or methacrylic polymers or copolymers, carboxyvinyl polymers, polyglyceryl acrylates or polyglyceryl methacrylates.

12. 12. The composition according to claim 1, wherein the aqueous medium comprises water and optionally one or more organic solvents that are soluble in water at 25°C.

13. 13. A method for cleansing the skin and / or skin appendages, comprising the step of applying to the skin and / or skin appendages a composition according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Skin cosmetic

    JP1998330211A

  • Emulsified cosmetic

    JP2003055129A

  • O / W emulsified composition

    JP2003192532A